The last kings of Qatna - Turri, Luigi (Le fleuve rebelle, 2016)
Despite its early identification with the modern Mishrifeh and its numerous mentions in Akkadian, Egyptian and Hittite texts, the history of Qatna remains largely unknown. This article attempts to reconstruct the landscape and the history of the city between the 15th and 14th cent. In this reconstruction it is assumed that the expression “the Lands of Nuhashe”, that occurs frequently in the texts, had two different meanings, a geographical one and a political one. In this way, the identification of the Addu-nirari mentioned in the texts found at Qatna with the homonymous king of EA 51, proposed by Thomas Richter, can be accepted, but without the need to assume that he was also king of a coalition called Nuhashe. During his reign and those of his successors, Idanda and Akizzi, the city faced many threats from the great kingdoms of Egypt and Hatti, as well as from the small neighbouring kingdoms. Their struggle for survival and a couple of political turnovers were not enough to let the city outlive those turbulent years.